Alpha-Enolase: Emerging Tumor-Associated Antigen, Cancer Biomarker, and Oncotherapeutic Target - Almaguel, Frankis A.; Sanchez, Tino W.; Ortiz-Hernandez, Greisha L.; Casiano, Carlos A. (Frontiers in Genetics, 2021)
Alpha-enolase, also known as enolase-1 (ENO1), is a glycolytic enzyme that “moonlights” as a plasminogen receptor in the cell surface, particularly in tumors, contributing to cancer cell proliferation, migration, invasion, and metastasis. ENO1 also promotes other oncogenic events, including protein-protein interactions that regulate glycolysis, activation of signaling pathways, and resistance to chemotherapy. ENO1 overexpression has been established in a broad range of human cancers and is often associated with poor prognosis. This increased expression is usually accompanied by the generation of anti-ENO1 autoantibodies in some cancer patients, making this protein a tumor associated antigen. These autoantibodies are common in patients with cancer associated retinopathy, where they exert pathogenic effects, and may be triggered by immunodominant peptides within the ENO1 sequence or by posttranslational modifications. ENO1 overexpression in multiple cancer types, localization in the tumor cell surface, and demonstrated targetability make this protein a promising cancer biomarker and therapeutic target. This mini-review summarizes our current knowledge of ENO1 functions in cancer and its growing potential as a cancer biomarker and guide for the development of novel anti-tumor treatments.